EVALUATION PRACTICES IN REGULAR EDUCATION - de Araújo Soares Santos, Viviane (Revista Gênero e Interdisciplinaridade, 2024)
The present work aims to present a new teaching-learning evaluation methodology in regular education in Brazil, highlighting the competency-based methodology, as a practice that evaluates the student’s learning evolution and not just a grade, which will include you at a higher level of education. To this end, a qualitative and exploratory approach was used to demonstrate that knowledge can be acquired and absorbed, through playful activities, knowledge of experience, external explorations, in addition to classrooms, among others. From this it was possible to see how the content was assimilated by the students and how their skills were exposed in their daily actions.